Chronic herpesvirus reactivation occurs in aging - Stowe, Raymond P.; Kozlova, Elena V.; Yetman, Deborah L.; Walling, Dennis M.; Goodwin, James S.; Glaser, Ronald (Experimental gerontology, 2007)
The aged immune system is characterized by clonal expansions of CD8+ T cells of which a substantial portion are directed against Epstein-Barr virus (EBV) and cytomegalovirus (CMV). It is unknown if these expansions represent increased viral reactivation or simply reflect an accumulation over time. We investigated herpesvirus reactivation in young and old subjects co-infected with CMV and EBV. Using molecular and serological techniques, we found significant increases in both the frequency and magnitude of EBV and CMV reactivation in elderly subjects. CMV DNA was frequently detected in the urine of elderly subjects; EBV load in peripheral blood was also significantly increased. Notably, EBV DNA in plasma was detected in a majority of the elderly subjects which was supported by frequent transcription of late structural genes. Furthermore, CD8+ T cells specific for EBV structural antigens were detected in samples from the elderly. Samples from our younger control group were negative for EBV DNA in plasma, CMV DNA in urine, expression of structural transcripts, and lacked CD8+ T cells specific for EBV structural antigens. These findings indicate that the aged immune system is no longer able to control EBV and CMV reactivation that could now be characterized as chronic instead of latent.